Accumulation of Flavonols over Hydroxycinnamic Acids Favors Oxidative Damage Protection under Abiotic Stress - Martinez, Vicente; Mestre, Teresa C.; Rubio, Francisco; Girones-Vilaplana, Amadeo; Moreno, Diego A.; Mittler, Ron; Rivero, Rosa M. (Frontiers in Plant Science, 2016)
Efficient detoxification of reactive oxygen species (ROS) is thought to play a key role in enhancing the tolerance of plants to abiotic stresses. Although multiple pathways, enzymes and antioxidants are present in plants, their exact roles during different stress responses remain unclear. Here we report on the characterization of the different antioxidant mechanisms of tomato plants subjected to heat stress, salinity stress or a combination of both stresses. All the treatments applied induced an increase of oxidative stress, with the salinity treatment being the most aggressive, resulting in plants with the lowest biomass, and the highest levels of H2O2 accumulation, lipid peroxidation and protein oxidation. However, the results obtained from the transcript expression study and enzymatic activities related to the ascorbate-glutathione pathway did not fully explain the differences in the oxidative damage observed between salinity and the combination of salinity and heat. An exhaustive metabolomics study revealed the differential accumulation of phenolic compounds depending on the type of abiotic stress applied. An analysis at gene and enzyme levels of the phenylpropanoid metabolism concluded that under conditions where flavonols accumulated to a greater degree as compared to hydroxycinnamic acids, the oxidative damage was lower, highlighting the importance of flavonols as powerful antioxidants and their role in abiotic stress tolerance.